CD103 and CD39 coexpression identifies neoantigen-specific cytotoxic T cells in colorectal cancers with low mutation burden - van den Bulk, Jitske; van der Ploeg, Manon; Ijsselsteijn, Marieke E; Ruano, Dina; van der Breggen, Ruud; Duhen, Rebekka; Peeters, Koen C M J; Fariña-Sarasqueta, Arantza; Verdegaal, Els M E; van der Burg, Sjoerd H; Duhen, Thomas; de Miranda, Noel F C C (Journal for immunotherapy of cancer, 2023)
BackgroundExpression of CD103 and CD39 has been found to pinpoint tumor-reactive CD8+ T cells in a variety of solid cancers. We aimed to investigate whether these markers specifically identify neoantigen-specific T cells in colorectal cancers (CRCs) with low mutation burden.Experimental designWhole-exome and RNA sequencing of 11 mismatch repair-proficient (MMR-proficient) CRCs and corresponding healthy tissues were performed to determine the presence of putative neoantigens. In parallel, tumor-infiltrating lymphocytes (TILs) were cultured from the tumor fragments and, in parallel, CD8+ T cells were flow-sorted from their respective tumor digests based on single or combined expression of CD103 and CD39. Each subset was expanded and subsequently interrogated for neoantigen-directed reactivity with synthetic peptides. Neoantigen-directed reactivity was determined by flow cytometric analyses of T cell activation markers and ELISA-based detection of IFN-γ and granzyme B release. Additionally, imaging mass cytometry was applied to investigate the localization of CD103+CD39+ cytotoxic T cells in tumors.ResultsNeoantigen-directed reactivity was only encountered in bulk TIL populations and CD103+CD39+ (double positive, DP) CD8+ T cell subsets but never in double-negative or single-positive subsets. Neoantigen-reactivity detected in bulk TIL but not in DP CD8+ T cells could be attributed to CD4+ T cells. CD8+ T cells that were located in direct contact with cancer cells in tumor tissues were enriched for CD103 and CD39 expression.ConclusionCoexpression of CD103 and CD39 is characteristic of neoantigen-specific CD8+ T cells in MMR-proficient CRCs with low mutation burden. The exploitation of these subsets in the context of adoptive T cell transfer or engineered T cell receptor therapies is a promising avenue to extend the benefits of immunotherapy to an increasing number of CRC patients.